Evaluating the Role of ASEAN in Addressing Human Trafficking Against Migrant Workers: A Case Study of Myanmar and Thailand (2021-2025) - Desvitha Alviona Br. Sembiring; Ushwatul Jannah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Following the 2021 military coup in Myanmar, migrant workers became increasingly vulnerable to labor exploitation and human trafficking along the Myanmar–Thailand corridor. This study aims to evaluate the effectiveness of ASEAN in addressing human trafficking through regional mechanisms such as the ASEAN Convention Against Trafficking in Persons (ACTIP), ASEANAPOL, and Senior Officials Meeting on Transnational Crime. This research employs a qualitative method, and its analytical framework is based on the perspective of human security. The study shows that ASEAN has established various regional anti-trafficking instruments; however, their implementation still faces challenges such as the dominance of the non-intervention principle, weak regional coordination, and differences in the capacities of member states. In addition, ASEAN’s attention remains focused on state security rather than the direct protection of victims. This study argues that ASEAN needs to strengthen a human-centered security approach in order to protect migrant workers, who constitute a vulnerable group.